2009
DOI: 10.1177/039463200902200201
|View full text |Cite
|
Sign up to set email alerts
|

Pidotimod: A Reappraisal

Abstract: Pidotimod (Polimod ®) is a synthetic dipeptide molecule with biological and immunological activity on both the adaptive and the innate immune responses. In vitro studies, both from animal and human specimens, have documented a good activity on innate and adaptive immune responses and have been confirmed by in vivo studies. These activities have been applied in clinical studies demonstrating the efficacy of pidotimod in reducing the rate of recurrent infections of the upper respiratory and urinary tracts in chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 7 publications
0
20
0
1
Order By: Relevance
“…15,16 In vitro studies, both from animals and human specimens, have documented good activity on innate and adaptive immune responses, and have been confirmed by in vivo studies. The previous studies also demonstrated that PTD itself did not have antibacterial activity, but when combined with antibacterial agents could be effective in improving clinical symptoms of patients, promoting recovery and shortening hospital stay.…”
Section: Synergistic Effect Of Methionine Encephalin (Menk) Combined mentioning
confidence: 87%
See 1 more Smart Citation
“…15,16 In vitro studies, both from animals and human specimens, have documented good activity on innate and adaptive immune responses, and have been confirmed by in vivo studies. The previous studies also demonstrated that PTD itself did not have antibacterial activity, but when combined with antibacterial agents could be effective in improving clinical symptoms of patients, promoting recovery and shortening hospital stay.…”
Section: Synergistic Effect Of Methionine Encephalin (Menk) Combined mentioning
confidence: 87%
“…So it is crucial to understand the regulation of DC maturation to gain further insight into their in vivo function. [21][22][23][24][25] Both MENK and PTD are peptide molecules of TH1 modulatiors, 5,16 and each of these peptides, when used separately, promotes functional maturation of dendritic cells and have a marked effect on suppressing the progression of some tumors. 26,27 Whether these two peptides exert synergistic effect on DCs remains unclear so far.…”
Section: Synergistic Effect Of Methionine Encephalin (Menk) Combined mentioning
confidence: 99%
“…Interestingly, these effects are more evident in the setting of immune defects such as senescence, downs syndrome, and cancer. Researches have also demonstrated that pidotimod itself does not have antibacterial activity, but when combined with antibacterial agents, pidotimod can be effective in improving clinical effects, promoting recovery, and shortening therapy time 6,7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Pidotimod (3-L-pyroglutamyl-L-thiaziolidine-4carboxylic acid) is a synthetic dipeptide molecule with immunomodulatory properties [14]. It is a highly purified molecule with high reproducibility among batches.…”
Section: Introductionmentioning
confidence: 99%